181k views
0 votes
Help please thank you

Help please thank you-example-1
User PhysicalEd
by
5.2k points

1 Answer

2 votes

Answer:

g(1) = -6

Explanation:

g(x) = -2x^2 - 4x

You want to solve for g(1). To do this make every x value in the original equation become 1.

g(1) = -2(1)^2 - 4(1)

Evaluate the exponent.

g(1) = -2(1) - 4(1)

Multiply.

g(1) = -2 - 4

Subtract.

g(1) = -6

User HomerThinking
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.